الإضترابات اللغوية في الدراما الكورية Extraordinary Attorney Woo : دراسة اللغوية النفسية - Sayyidaturrohimah Sayyidaturrohimah; Luthfiyyatin Niswah; Nur Ila Ifawati (Lisanudhad: Jurnal Bahasa, Pembelajaran, dan Sastra Arab, 2023)
Abstract This study aims to describe the language disorder experienced by the character Woo Young Woo in the Korean drama Extraordinary Attorney Woo. The research method used is qualitative descriptive with data collection techniques, see notes and data analysis techniques, data reduction, data presentation, and conclusions. This Korean drama is directed by Yoo In-Shik and the script of the drama is written by Moon Ji-Won. The results of the research obtained are the character Woo Young Woo is said to have autism spectrum. However, he has extraordinary intelligence with an IQ of 164. This distinguishes between him and people with autism in general. So, it was concluded that the type of disorder Woo suffered from was spectrum Asperger's. Some of the symptoms of autism syndrome experienced by Woo are talking about one topic that he likes continuously, often repeating the same words, flat tone and voice like a robot, too fast in explaining things, not making eye contact and avoiding physical contact, less sensitive to the meaning of emotions and expressions of people around him, difficult to make friends, sensitive to light and noise,  has difficulty coordinating movements, is a perfectionist, and has an above-average IQ. Keywords: Language disorder, Korean drama, Asperger's syndrome, Psycholinguistics.